Male Students Perspective Regard their Learning Experience During the Clinical Course of Maternity Health Care - Basel Zawaw; Omar Sawalmeh; Anees SHhab; Yazeed Abu Tammam (My University, 2013)
Background: Nursing as profession historically was considered as a feminine and socially job, number of male entering the profession is recently changed and increased. Culture and population background and religion might have its impact on health care provision, some cultures may considered those who working with female as gay, other cultures don’t prefers working and caring with mothers and women from religion point of views, other might accept some type of caring and not accepting other aspects of care especially that considered invading of intimate space of mothers. The aim of this study: Was to explore the male student nurse's experience of the clinical maternity course. Methodology: It was a descriptive quantitative design study. The sample was convenient sample that randomly selected from the 4 universities that teach nursing of total 77 students who completed their maternity course. The tool was self administrative questionnaire composed of 6 parts; demographic data, gender preferences and related perception, common problems, students clinical experience and suggestions. All students were reached at their universities. Data was analyzed used SPSS software. Results: The results revealed that there were no significant differences between universities in relation to the students’ experience, factors and problems faced them. It also showed that high percentage of students didn’t perform the most embarrassing procedures in maternity such as vaginal examination, assessment of perineum, and attending or assist in normal vaginal delivery especially in private hospitals. Whereas the less embarrassing procedures such as abdominal examination, fetal heart auscultation, and educational sessions were done by most of students. Recommendation: Changes and actions have to be taken at level of universities and training areas to further involve male student nursing in women care